The gut–adipose/pancreas axis: a novel perspective on glycolipid metabolism dysregulation in MAFLD and T2DM pathogenesis - Liang, Jiahui; Chen, Xingyu; Chu, Yunhang; Leng, Yan (Frontiers in Endocrinology, 2025)
Metabolic-associated fatty liver disease (MAFLD) and type 2 diabetes mellitus (T2DM) frequently co-exist on the pathological basis of dysregulated glucose and lipid metabolism, forming a bidirectional causal relationship. The upstream mechanisms underlying this association require further elucidation. Recent studies suggest that the interactive network comprising the “gut–adipose axis” and “gut–pancreatic axis” represents a core component of the comorbidity mechanism. This network initiates with gut microbiota dysbiosis, which alters short-chain fatty acids (SCFAs), lipopolysaccharide (LPS), branched-chain amino acids (BCAAs), secondary bile acids(SBAs), and other microbial metabolites, as well as endocrine signals such as the endocannabinoid system (ECS) and incretin hormones. This network simultaneously influences adipose tissue and the pancreas to coordinate glucose and lipid homeostasis. Therefore, this paper proposes the “Common Messengers, Dual-Axis Convergence” model to systematically elucidate how the gut microbiota, through a shared set of messenger molecules, simultaneously and independently drives lipid and glucose metabolic dysregulation via the gut–adipose and gut–pancreatic axes, ultimately leading to the comorbidity of MAFLD and T2DM.